An Evaluation of Scholarly Works of Tax Incentives in Indonesia : Bibliometric Analysis of Policy Learning - Ririn Riani; Aam Slamet Rusydiana (SMART Insight, 2022)
Over the years, the issue of tax policy design has been a major concern requiring extensive scientific research. In light of these considerations, the purpose of this paper is to investigate the extent to which prior research has focused on tax incentives in Indonesia. This paper employs bibliometric analytic techniques to examine the empirical literature published between 1987 and 2023. This paper utilizes the Scopus database and the